Improvement of Malay Rumi Writing Skills Among Mattayom 1 Students at Saengthamwittaya Foundation School - Yenti Deslina; Devinna Riskiana Aritonang; Eli Marlina Harahap; Husniah Ramadhani Pulungan; Lili Herawati Parapat (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to describe students’ initial and final abilities in using animate and inanimate nouns in Malay Rumi compositions and to examine the improvement in writing skills after the implementation of structured instructional treatment. The research employed a Classroom Action Research (CAR) method with a pretest–posttest design involving 39 Mattayom 1 students at Saengthamwittaya Foundation School, Southern Thailand. The research instrument consisted of essay writing tasks with personal themes such as “My Family,” “My School,” and “My Best Friend,” which were analyzed based on the accuracy of noun classification and usage. The findings indicate that the mean pretest score of 73.39 increased to 82.59 in the posttest, reflecting a gain of 9.2 points. This improvement demonstrates that structured instruction integrating explicit grammar teaching, process-based writing practice (planning, drafting, revising, and editing), and corrective feedback effectively enhances students’ writing skills. In addition to quantitative improvement, qualitative progress was also observed, including a reduction in noun classification errors and greater consistency in sentence structure. These findings confirm that Classroom Action Research based instructional intervention can improve linguistic accuracy while simultaneously strengthening students’ metacognitive awareness in writing Malay Rumi.